The food and feeding habits of greenback grey mullet, Liza subviridis (Valenciennes), from different habitats and at various stages of growth - Chan, E.H.; Chua, T.E. (Wiley, 1979)
An analysis of the stomach contents of Liza subviridis at various stages of growth and from different habitat types is given. Transitions in diet with respect to size were observed. Postlarval stages of less than 12 mm standard length fed only on zooplankton. The transition to bottom feeding occurred in specimens 16–20 mm, with food items consisting of zooplankton, diatoms, detrital material and inorganic sediment. The transition was complete on attaining a length of 24 mm whereby food items comprised diatoms, detrital material, filamentous algae and inorganic sediment. The relevance of this information in aquaculture is discussed. The stomach contents of adult Liza subviridis taken from different habitat types were consistent, comprising diatoms, detrital material and inorganic sediment. Filamentous algae was also consumed where available.